2009
DOI: 10.1111/j.1600-0404.1994.tb02708.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain involvement in myotonic dystrophy: MRI features and their relationship to clinical and cognitive conditions

Abstract: A prospective, case‐control study was carried out on 25 patients with myotonic dystrophy (MyD) and 25 healthy subjects using brain magnetic resonance imaging (MRI). The frequency and severity of white matter hyperintense lesions (WMHL) and brain atrophy in MyD patients were compared with their clinical features and cognitive impairment using an extensive neuropsychological battery. Eighty‐four per cent of MyD patients showed WMHL, compared with 16% of controls (p<0.0001). These lesions involved all cerebral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…White matter changes and cerebral atrophy have been shown [19][20][21][26][27][28][29][30][31][32][33][34]. In a morphometric study, we have shown that frontal and prefrontal cortices are among the cortical areas selectively involved in the gray matter atrophy in DM1 [24].…”
Section: Introductionmentioning
confidence: 87%
“…White matter changes and cerebral atrophy have been shown [19][20][21][26][27][28][29][30][31][32][33][34]. In a morphometric study, we have shown that frontal and prefrontal cortices are among the cortical areas selectively involved in the gray matter atrophy in DM1 [24].…”
Section: Introductionmentioning
confidence: 87%
“…Frontal lobe motor areas and the prefrontal cortex are involved in strategic planning tasks. Earlier reports had documented a significant impairment of frontal lobe function, 14,24 as is typical of a dysexecutive syndrome. Several authors tried to correlate neuropsychological and neuroimaging findings.…”
Section: Global Intelligencementioning
confidence: 96%
“…There has been inconsistency in interpreting these white matter hyperintense lesions and no general agreement as to their clinical relevance. Some authors do not find a clinical correlate to the neuroimaging profile, 14 whereas others find a correlation between neuropsychological data and the distribution and severity of white matter abnormalities. 24,45,111 We found no correlation between the degree of cerebral involvement on traditional MRI studies and cognitive and behavioral profiles.…”
Section: Neuroimaging Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…Age of disease onset ranged from 5 to 67 years (mean 37.6 ± 19.2 years), with an estimated disease duration of 16.3 ± 10.2 years. Mean educational level was 10 ± 5 years (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. None of the selected subjects presented a clinical history of other neurological diseases affecting muscle or cognitive functions, alcohol or drug abuse; thyreotoxicosis or diabetes were further exclusion criteria.…”
Section: Dm2mentioning
confidence: 99%